THE INFLUENCE OF MANAGEMENT INFORMATION SYSTEM QUALITY ON USER SATISFACTION AND EMPLOYEE PERFORMANCE IN LOCAL GOVERNMENT AGENCIES - Saidatun Nuri; Munasarah; Rayyan Firdaus (RADJA PUBLIKA, 2025)
This study aims to examine the effect of Management Information System (MIS) quality on user satisfaction and employee performance in local government agencies. Using a literature study approach, this study collects and analyzes secondary data from various sources such as scientific articles and academic reports to identify the relationship between MIS quality, user satisfaction, and employee performance. The results of the study indicate that MIS quality including reliability, ease of use, access speed, and data security have a significant effect on user satisfaction and employee performance. Thus, improving the quality of MIS is expected to improve the efficiency, effectiveness, and quality of public services in local government agencies.